Production and evaluation of activated carbon from Saudi Arabian Acacia Tortilis tree bark by microwave and low temperature activation process - Muhammad Saleem (Yanbu Journal of Engineering and Science, 2023)
In the present work, activated carbon was produced from Acacia Tortilis tree bark, utilizing phosphoric acid chemical activation, and microwave irradiation (AC-MWI). Activated carbon was also produce by conventional phosphoric acid chemical activation and low temperature carbonization (AC-CA). Characterization of produced activated carbons performed by proximate analysis adopting ASTM standard procedures. BET-specific surface area, total ash content, bulk density, moisture content, pH, pore volume and iodine number were determined. Comparison of characteristics for both carbon, with the characteristics of AC available in the literature and commercially available in the market was performed. Comparison showed that activated carbon produced from Acacia Tortilis tree bark is well comparable with the reported characteristics of AC in literature and commercially available in market. It was found that AC-MWI has higher BET-specific surface area than AC-CA (836 m2/g and 687 m2/g respectively). Results depict that there is an increase of 22.3% in microspores component and 21.7% BET- specific surface area obtained in AC-MWI as compared to AC-CA. Similarly, the corresponding pore volume obtained (4.97 cm3/g and 4.07 cm3/g respectively) demonstrating better values as compared to the commercial ACs (<1 cm3/g). Additionally, it was found that AC can be produced by microwave irradiation in about 48.5% less time when compared to conventional low temperature heating. The adsorption study of produced ACs was performed using methylene blue as a contaminant. Study showed that MB removal rate initially increased with increase in contact time, which decreased with time until steady state was reached. Adsorption data of MB was fitted to Freundlich, Langmuir and Temkin adsorption isotherm models. All models show reasonable correlation, however, Freundlich isotherm is best to describe the MB adsorption on AC-MWI based on correlation coefficient R2 value (0.9985). The results revealed the feasibility of microwave heating for preparation of high surface area activated carbons from Acacia Tortilis tree bark.